Dynamics of erosion-accumulation processes along the stream bed of Turiya River (Kovel hydropost) - Pavlovska Т.; Kovalchuk, I.; Biletskyi, Yu.; Rudyk О.; Henaliuk, R. (Land Management, Cadastre and Land Monitoring, 2020)
The article reflects the results of the study of deformations of the stream bed of the Turiya River (Kovel Hydropost, hydro range No. 5) during 1983–2018. For this purpose, multiple cross-sections of the channel and various combined flow curves were constructed and analyzed, the levels of water in the river, the relationships between the course of erosion-accumulation processes along the course and the dynamics of natural and anthropogenic factors are revealed. The information base of the study was the theoretical basis of the doctrine of channel processes, which are substantiated in the works of foreign and Ukrainian scientists, the materials of our own observations, data from the Volyn Center for Hydrology and Meteorology (hereinafter VCGM). In the process of solving the tasks, the methods of comparative analysis, synthesis, graphic, mathematical and statistical methods were applied; the system approach was applied. During the study it was established that during the specified time interval in the stream bed there was an alternation of erosion and accumulation processes, which was expressed by the alternation of periods of some erosion of the stream bed and its siltation. The transverse profiles of the Turiya stream bed indicate that during the period 1983–1988, mainly accumulative processes prevailed in the channel, and in the following period (1988–2008) they changed to erosion ones. In recent years, rechargeable processes have become dominant and the profile of the stream bed in 2018 has come closer to its stream bed in 1988. The flow and water level curves of Turiya confirm our conclusions about trends in erosion-accumulation processes along the stream bed. During the periods 1983–1988 and 1996–2000, the accumulation processes dominated, and at the interval of time from 1988 to 1996 and in 2000–2008 erosion processes dominated. The 2009, 2012, 2013, 2014, 2017 curves are in almost one field, which attests to the stability of the Turiya River over the last decade. The development of channel deformations depends, mainly, on the hydrological regime of the river. The dynamics of erosion-accumulation processes along the river Turiya is consistent with the long-term regime of its maximum runoff: in the 80-ies of the last century a significant fall in the values of maximum discharge (some decrease in annual precipitation, the influence of the Kovel reservoir) was observed, which led to their erosion. Compared to this time period, around the 1990s and during the 2000s, the values of maximum discharge increased slightly. As a consequence, the eroding ability of the watercourse during floods and freshets increased, which slightly increased the cross-sectional area of the channel. In the last four years, the values of maximum discharge have been significantly lower than normal, and as a result erosion processes have weakened. Reduction of the maximum discharge of the Turiya River, absence of runoff during the 2015–2018 boundary, dominance of accumulative processes in the channel leads to eutrophication of the watercourse, which, in turn, reduces its transport capacity and contributes to the further accumulation of solids. If this trend continues in the future, then the risks of flooding the Turiya floodplains in the event of heavy floods or freshets will increase. Keywords: Volyn region, hydrological regime, hydropost, water flow and water level curves, transverse profile of river bed, Turiya River, surface runoff, stream bed deformations.